JENIS-JENIS BAKTERI PADA LUKA IKAN PATIN (Pangasius djambal) - Yudha Perdana Putra Lubis; Yunasfi Djayus; Rusdi Leidonald (AQUACOASTMARINE, 2014)
One of the various forms of business which produces fish optimally and do not damage fish populations and environment is a good freshwater fish farming. Currently catfish become one of the leading commodity in the fishery. Bacterial diseases arising from injury affecting the outcome of catfish farming. This research had been conducted on September – October 2013. It purpose was to determine the type of bacterias that commonly found in catfish (Pangasius djambal) wound. Sampling was done one time to collect 10 fishes. Samples were fishes which showed of clinical symptoms such as wound, skin discoloration, defect on the fins, tail and antennae, slow-moving, swim on the surface, tend to be solitary (not clustered ) and also fish without no clinical symptoms. Bacteria only found in injury catfish they are Aeromonas hydrophilla, Pseudomonas aeruginosa, Pseudomonas pseudomallei and Morganella morganii.Keywords: Catfish (Pangasius djambal), Fish disease, Types of Bacterias, Wound.